The role of implicit semantic components during the synthesis of russian verbal modifications (a case study for the verbs of mechanical phonation) - Ivlieva I. V. (Interactive science, 2019)
the article examines the implicit components in the meaning of semantically modified derivatives. Using the methods of componential analysis of definitions from various Russian explanatory and aspectual dictionaries, the implicit components in the sound verbs’ meanings are inventoried. The impact of the relevant implicit components on the synthesis process is examined; the dichotomy of the implicit components of meaning and corresponding synthesizing prefixes is identified. The productivity and typical colloquial usage of synthesized derivatives is demonstrated using data from the Russian National Corpus.
Keywords: дефиниционный анализ; модификация; имплицитность; синтез русского глагола; глаголы звучания; verbs of sound; verbal modifier; modification; модификатор; Национальный корпус русского языка; имплицитное значение; механическая фонация; implicitness; implicit meaning; definitions’ analysis; synthesis of Russian verbs; mechanical phonation; the Russian National Corpus